A study for the Assessment of Nutritional Deficiency Status of the School Going Girls - Archana Singh; Rashmi Sharma (Integrated Journal for Research in Arts and Humanities, 2022)
Nutrient deficiencies are prevalent worldwide. Nutritional status refers to a person's overall health, which is impacted by nutrient intake and use in the body. Children between the ages of 6 and 12 are commonly regarded to be of school age, and this might be a second chance to make up on growth. Children's nutritional condition reflects not only the family's financial position and community's social well-being but also the health-care system's productivity and the effect on the surroundings. The present study reveals that the school going girls are suffering from different nutritional deficiencies like- anaemia, underweight, overweight, obesity, stunting, iodine deficiency etc. These deficiencies are emerging health problems and become the major epidemic cause of serious health problems in India. Children's diets in India, like those in many other wealthy nations, are often imbalanced, with an overabundance of calories and protein and insufficient amounts of numerous minerals and vitamins.